毎分写真撮影評価法による木造軸組工法住宅の施工人工数調査 - 稲山 正弘; 大澤 一実; 蟹澤 宏剛; 相馬 智明; 大澤 宏實 (住宅総合研究財団研究論文集, 2011)
About the fixtures construction of the wooden house, we performed spot investigation with ”every share photography evaluation law”that we developed originally. Based on findings, we inspected it about the execution rationalization technique of the flooring. As a result, rationalization superiority was found by flooring precedent execution by the skeleton infill structure. We clarified a change of the use frequency about tools and nails, others. In addition, we specified the rate of operation of the construction spot and the change factor. 木造軸組工法住宅の施工，特に大工を中心とした内装造作工事における生産性を確認するため，「毎分写真撮影評価法」を開発・試行した。その上で，構法・施工手順の異なる２棟の新築現場について施工状況調査と比較を行った。2現場とは，間仕切耐力壁があり，間仕切壁先行施工・床後張施工の従来型方式による「一般棟」と，間仕切耐力壁がなく，床先行施工・間仕切壁後施工の「SI分離型棟」であり，施工手順の違いによる生産性の違いを確認した。その結果，SI分離型施工において一定の施工合理化効果が認められた。また，本評価法を用いて，工具の使用量推移や，工種ごとの要素作業量の集計などが可能であることを示し，その汎用性を示した。